2015
DOI: 10.1016/j.seizure.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

How important is the seizure onset zone for seizure dynamics?

Abstract: Our findings underline the high relevance of brain outside of the SOZ but within the large-scale epileptic network for seizure dynamics. Knowledge about these network constituents may elucidate targets for individualised therapeutic interventions that aim at preventing seizure generation and spread.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 57 publications
4
51
0
3
Order By: Relevance
“…Other studies only reported an increase in the betweenness centrality in the gamma band (Varotto, Tassi, Franceschetti, Spreafico, & Panzica, 2012; Wilke et al, 2011), or in a few seconds prior to seizure onset (Li et al, 2016). Geier, Bialonski, Elger, and Lehnertz (2015) found that the betweenness centrality in pre‐ictal ECoG (using cross‐correlation) was highest in brain regions neighboring the SOZ. This idea is supported by results for one of our patient, see the example in (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies only reported an increase in the betweenness centrality in the gamma band (Varotto, Tassi, Franceschetti, Spreafico, & Panzica, 2012; Wilke et al, 2011), or in a few seconds prior to seizure onset (Li et al, 2016). Geier, Bialonski, Elger, and Lehnertz (2015) found that the betweenness centrality in pre‐ictal ECoG (using cross‐correlation) was highest in brain regions neighboring the SOZ. This idea is supported by results for one of our patient, see the example in (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the resected area of Patients 6-7 had no overlap with the marked SOZ, which posed the question: How reliable is the visually marked SOZ in such cases? Although the relationship between the SOZ resection and the post-surgical outcome is challenged by recent studies (Rummel et al, 2015;Geier et al, 2015;Huang et al, 2012), it is generally agreed that resection of critical parts of the SOZ is a sufficient condition to attain long-term seizure freedom (Rosenow and Lüders, 2001). Under this premise, we first assumed that the true SOZ of these patients had not been resected.…”
Section: Seizure Onset Identification and Retrospective Interpretationmentioning
confidence: 99%
“…A mechanistic understanding of seizure generation and evolution may be derived from spatial and temporal dynamics of the epileptic network (Wendling et al, 2003; Jerger et al, 2005; Schindler et al, 2007; Schevon et al, 2007; Schindler et al, 2008; Zaveri et al, 2009; Kramer et al, 2010; Jiruska et al, 2013; Rummel et al, 2013; Weiss et al, 2013; Burns et al, 2014; Geier et al, 2015; Khambhati et al, 2015, 2016). In this framework, network nodes are intracranial sensors measuring the electrocorticogram (ECoG) and network connections are time-varying statistical relationships between sensors (Friston, 2011; Hutchison et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of connectivity between brain regions is related to the synchronization of neural populations, a putative generator of dysfunction in epilepsy. Brain regions that are topologically central to the epileptic network tend to lie within (Wendling et al, 2003; Jerger et al, 2005; Schindler et al, 2007, 2008; Kramer et al, 2010; Jiruska et al, 2013; Burns et al, 2014; Khambhati et al, 2015) and adjacent to (Schevon et al, 2007; Zaveri et al, 2009; Rummel et al, 2013; Weiss et al, 2013; Geier et al, 2015) clinically defined seizure-onset zones (SOZs) during interictal, preictal, and ictal epochs (Zaveri et al, 2009; Warren et al, 2010; Khambhati et al, 2015). In this context, it is interesting to ask the question: if network dysfunction persists over long time scales, then (1) how does network topology drive brain dynamics differently during interictal and ictal epochs, and (2) how might aberrant brain regions disrupt functional interactions underlying normal function?…”
Section: Introductionmentioning
confidence: 99%